2015
DOI: 10.1371/journal.pone.0134505
|View full text |Cite
|
Sign up to set email alerts
|

Mesopic Functional Visual Acuity in Normal Subjects

Abstract: To evaluate mesopic functional visual acuity (FVA) with a newly developed system in normal subjects and to compare the results with photopic FVA, sixty-eight healthy volunteers (24.03 ± 4.42 [mean ± standard deviation] years) were enrolled in this study. A commercially available FVA measurement system (AS-28; Kowa, Aichi, Japan) was modified to measure FVA under mesopic conditions as well as photopic conditions. Measurements were performed monocularly in photopic conditions during 60 seconds. After dark adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 57 publications
(60 reference statements)
1
26
1
Order By: Relevance
“…While some researchers use a conservative adaptation period of 30 minutes (Yoshimoto, Okajima, & Takeuchi, 2016), others measuring mesopic sensitivity as a qualifying measure reveal that only 5 minutes are sufficient to allow dark adaptation (Perez, Puell, Sanchez, & Langa, 2003;Hertenstein, Bach, Gross, & Beisse, 2016). The participants in this study completed approximately 20 minutes of dark adaptation, which should be sufficient for our study parameters (Eloholma, Ketomäki, Orreveteläinen, & Halonen, 2006;Hiraoka, Hoshi, Okamoto, Okamoto, & Oshika, 2015;Koefoed, Baste, Roumes, & Hovding, 2015).…”
Section: Stimuli and Proceduresmentioning
confidence: 97%
“…While some researchers use a conservative adaptation period of 30 minutes (Yoshimoto, Okajima, & Takeuchi, 2016), others measuring mesopic sensitivity as a qualifying measure reveal that only 5 minutes are sufficient to allow dark adaptation (Perez, Puell, Sanchez, & Langa, 2003;Hertenstein, Bach, Gross, & Beisse, 2016). The participants in this study completed approximately 20 minutes of dark adaptation, which should be sufficient for our study parameters (Eloholma, Ketomäki, Orreveteläinen, & Halonen, 2006;Hiraoka, Hoshi, Okamoto, Okamoto, & Oshika, 2015;Koefoed, Baste, Roumes, & Hovding, 2015).…”
Section: Stimuli and Proceduresmentioning
confidence: 97%
“…42 Participants were given a 10-minute adaptation period to the mesopic light level based on previous study adaptation periods. 35,38,40,42,52 Visual Acuity and Contrast Sensitivity. Mesopic HCVA and Pelli-Robson CS were measured with the same method as the photopic assessments, using an alternative chart to avoid familiarity with the test letters.…”
Section: Mesopic Testsmentioning
confidence: 99%
“…31 A clinical examination of vision typically involves assessment of high contrast visual acuity (HCVA) under photopic light levels, which does not fully capture the visual capacity required for safe driving, 32,33 or for other lighting conditions such as the low luminance and glare conditions typically present when driving at night. [34][35][36][37] Numerous studies have demonstrated the advantages and advocated the use of Copyright 2017 The Authors iovs.arvojournals.org j ISSN: 1552-5783 nonstandard vision tests to represent visual function across a range of lighting conditions. 2,34,[38][39][40][41][42][43][44] While there is some evidence that driver safety and performance at night is associated with mesopic visual function and glare sensitivity, such as the Mesotest (mesopic CS in the presence and absence of glare) 45,46 and mesopic visual acuity (VA), 32 there has been very limited research into nighttime driving ability and the assessment of visual capacity to drive at night.…”
mentioning
confidence: 99%
“…; Hiraoka et al. ). While measures of contrast sensitivity (Wood & Owens ), mesopic visual acuity (VA) (Kimlin et al.…”
Section: Introductionmentioning
confidence: 96%